Mangrove sediments-associated bacterium (Bacillus sp. SW7) with multiple plant growth-promoting traits promotes the growth of tomato (Solanum Lycopersicum) - Afridi, Mahideen; Sadaiappan, Balamurugan; Nassar, Amna Saood; Mahmoudi, Henda; Khan, Munawwar Ali; Mundra, Sunil (Frontiers in Marine Science, 2024)
Global food production intensification presents a major hurdle to ensuring food security amidst a growing world population. Widespread use of chemical fertilizers in recent decades has risked soil fertility, compounded by the challenges posed by climate change, particularly in arid regions. To address these issues, adopting plant growth-promoting (PGP) bacteria stands out as a promising solution, offering multifaceted benefits to arid agroecosystems. We isolated a bacterial strain, SW7, from mangrove sediment, characterised the entire genome followed by phylogenetic analyses, and evaluated its in-vitro PGP activity. Subsequently, we examined its impact on tomato seed germination and plant growth. The strain SW7 exhibited growth on 11% NaCl, survival at 50°C, and possessed multiple PGP traits such as significant increase in seed germination rate (60.60 ± 38.85%), phosphate (83.3 g L−1) and potassium (39.6 g L−1) solubilization and produced indole acetic acid (3.60 ppm). Additionally, strain SW7 tested positive for ammonia, catalase, and oxidase enzyme production. The strain SW7 genome consists of 5.1 MB with 35.18% G+C content. Through genome-based phylogenetic and orthoANI analyses, the strain was identified as a novel Bacillus species, designated herein as Bacillus sp. SW7. In an eight-week shade-house experiment, inoculation of strain SW7 improved, leaf number, leaf density, leaf area index and mass water of tomatoes. Additional parameters, like chlorophyll a, chlorophyll b and carotenoids were not affected in SW7-inoculated tomatoes. In conclusion, Bacillus sp. SW7 exhibits multiple PGP traits and an adaptive capacity to high temperature and salinity, positioning it as a potential candidate for elevating the productivity of arid agroecosystems.